Annual patterns of stratification, mixing and ventilation in long, deep, seasonally ice-covered François lake, British Columbia, Canada - Vagle, Svein; Carmack, Eddy (Frontiers in Earth Science, 2023)
François Lake is a long, deep, seasonally ice-covered, dimictic lake set in an east-west orientation in mid-British Columbia. As a baseline we here present data from a full-depth temperature mooring deployed at the lake’s mid-point in 2004–2005 and one full-depth conductivity-temperature-depth cast. We use these temperature records to define lake stability, scales of motion and the annual cycle of thermal stratification, mixing and deep-water ventilation. Owing to its length (110 km) both the Wedderburn and Lake numbers—indices of thermocline tilt and mixing under wind forcing—transition through critical values during fall and spring seasons, suggesting thermocline outcropping and strong turbulent mixing within the thermocline at these times. Owing to its depth (240 m) the decreasing temperature of maximum density (TMD) with depth (thermobaric effect) adds complexity to overturn events. Owing to its seasonal ice cover (2–3 months per year) the critical period for effective fall ventilation occurs before ice formation and concurrent wind shielding, while that of spring ventilation lies between the dates that the ice cover melts and the lake surface water warms above 4°C. While the lake undergoes full depth ventilation in both fall and spring, we show that both progress in distinct dynamical stages. Fall ventilation is more efficient than that of spring, and the transition temperature and resulting bottom temperature from fall to winter stratification (positive to inverse) and winter to spring stratification (inverse to positive) lies close to the temperature of maximum density calculated for the maximum depth of free and forced convection (in this case, closer to 3.7°C).